Loneliness, lack of support, and educational challenges: teachers’ experiences working with refugee children - Lunina, Simona; Jurgilė, Vaida (Frontiers in Education, 2025)
For the first time, Lithuania has faced such a flow of refugee families with children, and it is natural that until now there is not enough experience and research in the education of refugee children in Lithuania. Until now, the focus has been on the integration and socialization of refugees, with very little attention paid to the education of refugee children in early childhood education settings. The education of refugee children and the opportunities to provide it globally became more important in 2022 when Ukrainian refugees were forced to flee their homes because of the war. This paper aims to reveal the experiences of Lithuanian teachers who, as soon as the war started, received refugee children in their classes without any prior information or adequate preparation. A study was carried out to uncover preschool teachers’ experiences of working with refugee children, so the following research questions are raised - what are the experiences of preschool teachers working with children with refugee status? What challenges do preschool teachers face? How do preschool teachers work with refugee children without official descriptions prepared by the State of Lithuania? A thematic analysis was applied. The results of the study revealed that pre-school teachers faced different educational challenges when educating refugee children: lack of foreign language skills, cultural differences, lack of support from professionals when working with refugee children, etc. The study found that teachers were intensively choosing self-initiated learning to improve their professional knowledge in order to ensure a quality education process for refugee children in early childhood education institutions. Teachers independently searched for suitable materials for the education of refugee children and adapted existing programs and guidelines to refugee children in their groups.